2017
DOI: 10.4338/aci-2016-09-ra-0154
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction and Improvements in Peritoneal Dialysis Outcomes Associated with Telehealth

Abstract: SummaryBackground and Significance: End stage renal disease (ESRD) affects approximately 660,000 persons in the US each year, representing a significant financial burden to the health care system and affected individuals. Telehealth approaches to care offer an important means of reducing costs as well as increasing autonomy for patients. Understanding patient satisfaction with telehealth provides a key towards eventual scalability. Materials and Methods: Quarterly surveys were conducted to characterize satisfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
92
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(104 citation statements)
references
References 14 publications
3
92
0
9
Order By: Relevance
“…Empowerment also reduced frustrations related to technological features [58,60]. COPD patients reported that the telehealth equipment lead to active engagement in health service provision and better access to healthcare [39].…”
Section: Evolving Independencementioning
confidence: 99%
“…Empowerment also reduced frustrations related to technological features [58,60]. COPD patients reported that the telehealth equipment lead to active engagement in health service provision and better access to healthcare [39].…”
Section: Evolving Independencementioning
confidence: 99%
“…As we have found in another telehealth study among a larger chronic disease population, 31 specialized video applications that offer face-to-face viewing may not be required to support patients remotely. Participants connected effectively with PHC staff via less novel telecommunication channels such as text, e-mail, and phone; video contact was not required.…”
Section: Discussionmentioning
confidence: 84%
“…Furthermore, high user satisfaction indicates that telehealth services are suitable for use in workplace health management. Unlike early telehealth, which only connected hospital and home, 13,22 this cloud-based telehealth platform can provide care at multiple locations, connecting community-based health care providers and patients across the lifecycle of care delivery-in the workplace, hospital, and at home.…”
Section: Discussionmentioning
confidence: 99%
“…7 There is a large body of evidence that supports the use of innovative technologies, such as telehealth, to monitor and manage chronic diseases such as diabetes, orthopedic conditions, human immunodeficiency virus/acquired immunodeficiency syndrome, or renal disease at a distance and as frequently as necessary. 4,[8][9][10][11][12][13] Although there has been a high level of interest in using technology in health care and significant growth is expected in this area, 14 implementation has not been without problems, and many of the forecasts have not yet been fully realized. 15,16 For example, many telehealth services that started with pilot or small-scale projects are not regularly maintained, 15,17,18 and telehealth is still not considered a mainstream activity in the health sector.…”
Section: Background and Significancementioning
confidence: 99%